Water-fluxed crustal melting and petrogenesis of largescale Early Cretaceous intracontinental granitoids in the southern Great Xing'an Range, North China - Li, S.; Chung, S.; Wang, T.; Wilde, Simon; Chu, M.; Pang, C.; Guo, Q. (Geological Society of America, 2018)
© 2017 Geological Society of America. We present a new petrogenetic model to explain the late Mesozoic large-scale magmatism in the southern Great Xing'an Range, North China. Why did voluminous magmatic activity over a wide region of Northeast China occur so dramatically in the Early Cretaceous? Here, we present new wholerock geochemical and Sr-Nd-Li isotopic data from a suite of dioritic-granitic rocks and insights into the petrogenesis and geodynamics of the large-scale Early Cretaceous granitoid magmatism in the southern Great Xing'an Range. These samples are enriched in large ion lithophile elements (LILEs) and light rare earth elements (LREEs) but depleted in Nb, Ta, and Ti for both the diorites and granitic suite, showing typical features of subduction-related magmas. The slightly low Nd values (ε Nd [t] = ~-0.5) and low 87 Sr/ 86 Sri values (~0.7056) of the diorites along with significant LILE and LREE enrichment indicate they probably evolved from mafic magmas metasomatized by slab melts or fluids. The variable Sri values (0.7050-0.7083) and negative to weakly positive ε Nd (t) values (-6.2 to +1.4) of the granitic suite suggest a dominantly old crustal source with involvement of mantle-derived materials in their generation. The granitic suite has variable d7Li values (+1.2‰ to +12.2‰), indicating their source had experienced heterogeneous hydration in response to deep fluid propagation. These Early Cretaceous granitoids have low Zr contents ( < 300 ppm) and low zircon saturation temperatures (T Zr < 800 °C), which are significantly lower than those expected for dehydration melting of mostly crust (T Zr > 800 °C), indicating their source was likely associated with the fluid from deep subducted slabs within the hydrous mantle transition zone. Fluid from hydrated stagnant slabs could catalyze and initiate waterfluxed crustal melting to produce hydrous granitic melts at 800-600 °C and 5-10 kbar, with 2-5 wt% H 2 O contents. Although we could not specify the true extent of stagnant paleo-Pacific slabs, the genesis of large-scale Early Cretaceous granitoids is essentially a snapshot of water-fluxed crustal melting in the southern Great Xing'an Range. Such melting could have played an important role in the Mesozoic deep crust architecture of Northeast Asia.